2020
DOI: 10.1063/1.5145316
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ferroelectric performance in PVDF:Fe3O4 nanocomposite based organic multiferroic tunnel junctions

Abstract: We report on the fabrication of organic multiferroic tunnel junction (OMFTJ) based on an organic barrier of Poly(vinylidene fluoride) (PVDF):Fe3O4 nanocomposite. By adding Fe3O4 nanoparticles into the PVDF barrier, we found that the ferroelectric properties of the OMFTJ are considerably improved compared to that with pure PVDF barrier. It can lead to a tunneling electroresistance (TER) of about 450% at 10K and 100% at room temperature (RT), which is much higher than that of the pure PVDF based device (70% at 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Several studies have shown the local piezoelectric properties of PVDF-TrFE copolymer neat films [33] as well as hybrid films based on the artificial mixing of the PVDF and copolymer phase with non-magnetic nano-phases (e.g., CNTs, ZnO, (Pb,Ba)(Zr,Ti)O 3 , graphene) [34][35][36][37][38][39]. Only very recent studies [40,41] have shown the possibility of using the magnetic phase organization inside the polymer matrix to improve the local PFM properties under the application of a magnetic field. Currently, these local PFM results have not provided the opportunity to understand the connection between the optimization of the macroscopic dielectric properties and the local electroactive one, both in the case of low loading and for the dispersion of the magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the local piezoelectric properties of PVDF-TrFE copolymer neat films [33] as well as hybrid films based on the artificial mixing of the PVDF and copolymer phase with non-magnetic nano-phases (e.g., CNTs, ZnO, (Pb,Ba)(Zr,Ti)O 3 , graphene) [34][35][36][37][38][39]. Only very recent studies [40,41] have shown the possibility of using the magnetic phase organization inside the polymer matrix to improve the local PFM properties under the application of a magnetic field. Currently, these local PFM results have not provided the opportunity to understand the connection between the optimization of the macroscopic dielectric properties and the local electroactive one, both in the case of low loading and for the dispersion of the magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pure PVDF fiber membrane cannot meet the operating requirements because of the weakness of the piezoelectric and service properties. Meanwhile, the inorganic dopant materials into PVDF is a simple and effective approach to enhance the piezoelectric properties of PVDF [18][19][20]. Therefore, it is quite crucial to prepare the inorganic-PVDF fiber membranes with better piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…[13] So, it is crucial to enhance the content of β phase in PVDF which is the fundamental aspect to materialize its ferroelectric performance in technological applications. There are many simple economical ways to enhance β-content in PVDF which is solely processing condition dependent for different application as reported by various reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. β -phase may be gained via solvent casting technique but when the material crystallized below 70 O C results high porosity [34].…”
Section: Introductionmentioning
confidence: 99%
“…[41] Similarly ferrites nanoparticles in PVDF enhances the tunneling electroresistances to 450% @10K and 100% in ambient condition room temperature (RT), which is quite excessive than those of the pure PVDF based device 70%@10K and 7% at RT in organic multiferroic tunnel junction (OMFTJ). [18] So, keeping all these in mind we have processed a very innovative, cost effective method of solution casting to fabricate free standing, flexible, light weight polymer nanocomposite with low filler loading of ferromagnetic CFO in ferroelectric PVDF to ignite the electro active phases in the composite for making suitable it for device application.…”
Section: Introductionmentioning
confidence: 99%